Sifat Fisik Dan Mekanik Mortar Dengan Penambahan Bakteri Baccilus Subtilis Pada Lingkungan Sulfat - Ilham, Muhammad; Djauhari, Zulfikar; Sitompul, Iskandar Romey (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
An aggressive environment can have an adverse impact on mortar, because there are reactive chemicals in that environtment. One of the chemicals that no need harmful to mortar is magnesium sulfate. This study used Bacillus Subtilis bacteria as an additive by studying physical and mechanical properties, as well as an innovation to restore mortar using bacteria called Self Healing mortar. In this study there were test objects in the form of a cube measuring 5 x 5 cm with a total of 84 samples. Physical and mechanical properties tests on normal water-immersed normal mortar, normal water-immersed bacterial mortar, and sulfate-water-immersed bacterial mortar were carried out at the age of 28 days and 56 days. The physical properties of the mortar test were sorptivity, unit weight and porosity, while the mechanical properties test testedwere compressive strength. The test results showed that the sorptivity value of the sulfate-soaked bacterial mortar was higher than the normal-water-soaked normal mortar and the normal-water-immersed bacterial mortar at the age of 28 days and 56 days, namely 0.1606 mm / min0.5 and 0.221 mm / min0.5. The results of the weight test showed that the sulfate water-immersed bacterial mortar was lower than the normal water-immersed normal mortar and the normal water-immersed bacterial mortar at the age of 28 days and 56 days, namely 2.002 gr / cm3 and 2.077 gr / cm3. The results of the porosity test showed that the value of the sulfate-immersed bacterial mortar was higher than that of the normal-water-soaked normal mortar and the sulfate-water-immersed bacterial mortar at the age of 28 days and 56 days, namely 14.96 % and 15.22 %, respectively. Meanwhile, in the compressive strength test, the value of the sulfate-immersed bacterial mortar was lower than that of the normal-water-immersed mortar and the normal-water-immersed bacterial mortar at the age of 28 days and 56 days, namely 17.13 MPa and 16.98 MPa, respectively. Based on the data obtained, it could be concludedsaid that bacillus subtillis bacteria couldn’t work well in a sulfate environment.Keywords: Mortar, Bacillus Subtilis, Sulfate Environment, Physical Properties, Mechanical Properties, Self Healing